Railway seminars the interaction of vehicle and track design : delegate information. (Thomas Telford, 1998)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a seminar held in Solihull on 20 May 1998.
Keywords: Railroad engineering -- Congresses.; elektronické knihy; electronic books